Growth process of molybdate conversion coating on the surface of aluminum foil and its adhesive mechanism. (16th August 2021) - Chen, Xinjie; Xu, Shiai
Abstract : In this study, an environmentally friendly molybdate (Mo) conversion coating was deposited on the surface of aluminum (Al) foil for use as the packaging film of lithium‐ion battery, and the surface morphology and chemical composition were characterized by field emission scanning electron microscopy (FE‐SEM), atomic force microscopy (AFM), energy dispersive spectroscopy (EDS), and X‐ray photoelectron spectroscopy (XPS). The XPS results show that the conversion coating is composed of MoO3, MoOx, Al2 O3, and (MoO3 )x (P2 O5 )y . Then, the effects of treatment time on the corrosion resistance of Al foil and the adhesive strength between Mo‐treated Al foil and maleic anhydride (MAH)‐grafted polypropylene (MPP) were investigated. It is revealed that both the peeling strength and the corrosion resistance of Mo‐treated Al foil increase with the treatment time.